2018
DOI: 10.1515/intag-2016-0089
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different soil management practices on soil properties and microbial diversity

Abstract: The effects of different tillage systems on the properties and microbial diversity of an agricultural soil was investigated. In doing so, soil physical, chemical and biological properties were analysed in 2013-2015, on a long-term field experiment on a loamy sand at the IUNG-PIB Experimental Station in Grabów, Poland. Winter wheat was grown under two tillage treatments: conventional tillage using a mouldboard plough and traditional soil tillage equipment, and reduced tillage based on soil crushing-loosening eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 29 publications
2
16
0
1
Order By: Relevance
“…Moreover, clay dispersibility is widely used to evaluate soil structural stability. A negative correlation was observed between clay dispersibility and SOC content, and NT (or reduced tillage) reduced the contents of clay dispersibility compared with CT (Gajda et al, 2018, 2021). Thus, it is concluded that NT could increase the clay content and decrease clay dispersibility, and thus promote soil aggregation and benefit SOC stability.…”
Section: Soc Stability Under Ntmentioning
confidence: 99%
“…Moreover, clay dispersibility is widely used to evaluate soil structural stability. A negative correlation was observed between clay dispersibility and SOC content, and NT (or reduced tillage) reduced the contents of clay dispersibility compared with CT (Gajda et al, 2018, 2021). Thus, it is concluded that NT could increase the clay content and decrease clay dispersibility, and thus promote soil aggregation and benefit SOC stability.…”
Section: Soc Stability Under Ntmentioning
confidence: 99%
“…Therefore, their density, activity, and diversity in soils are main factors in sustainable agriculture. Moreover, soil enzyme activities, particularly those associated to nutrient cycles, are important soil quality indicators that can measure the effects of tillage and are considered warning sensors of soil quality degradation (Gianfreda 2015;Gajda et al 2018;Lin et al 2018). Since the microbial and enzyme activity in soils vary according to soil management such as tillage and cropping, this presents an interesting question about their effect over chemical and biological characteristics of highland soils from Ecuador.…”
Section: Introductionmentioning
confidence: 99%
“…RT protects the sub-soil against compaction and erosion by water, can also increase the stability of the soil through increased SOC (Czyż and Dexter, 2009). RT has effects on soil physical properties: bulk density, water content (Fabrizzi et al, 2005;McVay et al, 2006;Mühlbachová et al, 2015Pabin et al, 2003Sławiński et al, 2012), soil stability Dexter, 2008, 2009); chemical: SOC (Gajda et al, 2017(Gajda et al, , 2018Małecka et al, 2015;Mikanová et al, 2012), available forms of P, K and Mg (Franzluebbers, 2002;Małecka et al, 2015); and increased biological activity (Gajda et al, 2017) and diversity of diatoms (Stanek-Tarkowska and Noga 2012a,b;Stanek-Tarkowska et al, 2015) compared with TT. Czyż and Dexter (2009) reported that RT decreased the content of readily dispersible clay (RDC) and therefore increased soil stability.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in Poland Kordas (2009) found the average yield of winter wheat in 3 years of monoculture to be lower under RT by 14.5% and under no-tillage by 15.9% compared with TT. Impacts of crop cultivation systems, agrotechnical treatments on crop yields, plant uptake of macronutrients and biodiversity of the ecosystem have also been observed (Gajda et al, 2017(Gajda et al, , 2018Kołodziejczyk et al, 2017;Mühlbachová et al, 2015).…”
Section: Introductionmentioning
confidence: 99%